2019
DOI: 10.1111/jedm.12213
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Partial Knowledge on Multiple‐Choice Items Using Elimination Testing

Abstract: Single-best answers to multiple-choice items are commonly dichotomized into correct and incorrect responses, and modeled using either a dichotomous item response theory (IRT) model or a polytomous one if differences among all response options are to be retained. The current study presents an alternative IRT-based modeling approach to multiple-choice items administered with the procedure of elimination testing, which asks test-takers to eliminate all the response options they consider to be incorrect. The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…was buying 2. was looking 3. is eating 4. cooks the ability to eliminate some, but not all, incorrect choices, thus restricting guessing to a proper subset of options that include the correct option (Frary, 1980;Frary & Hutchinson, 1982). Although previous studies have developed other procedures to evaluate partial knowledge, such as elimination testing (Coombs et al, 1956;Wu et al, 2019) and probability testing (Barr & Burke, 2013;Hassmén & Hunt, 1994), we focus on multiple-choice assessments and consider them within the CDM framework. It should be noted that the concept of partial knowledge differs from that of partial mastery (Shang et al, 2021;Zhan et al, 2020), which considers ordinal mastery levels within each attribute.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…was buying 2. was looking 3. is eating 4. cooks the ability to eliminate some, but not all, incorrect choices, thus restricting guessing to a proper subset of options that include the correct option (Frary, 1980;Frary & Hutchinson, 1982). Although previous studies have developed other procedures to evaluate partial knowledge, such as elimination testing (Coombs et al, 1956;Wu et al, 2019) and probability testing (Barr & Burke, 2013;Hassmén & Hunt, 1994), we focus on multiple-choice assessments and consider them within the CDM framework. It should be noted that the concept of partial knowledge differs from that of partial mastery (Shang et al, 2021;Zhan et al, 2020), which considers ordinal mastery levels within each attribute.…”
Section: Figurementioning
confidence: 99%
“…The literature has revealed that examinees frequently exclude some options from the possible answers based on their partial knowledge before guessing (e.g., Lindquist & Hoover, 2015). This behavior is referred to as educated guessing (Wu et al, 2021) or informed guessing (Tsai & Lin, 2017;Wu et al, 2019). Fitting the MC-DINA or MC-S-DINA models to the responses associated with partial knowledge would lead to the overestimation of attribute mastery states because the models that do not consider partial knowledge tend to under-evaluate the probability of correctly answering the items.…”
Section: Introductionmentioning
confidence: 99%